A Physiotherapy That Inhabits Time: Between Doing and Being Reflections for a More Human, Conscious, and Present Practice - de León Pérez, María Eugenia (Journal of Physiotherapy in Mental Health, 2025)
We live in a world where everything is urgent. Doing, creating, moving forward, never stopping… To the point where productivity has become the contemporary religion. Rest has been pathologized and is now viewed as a privilege, a waste of time, and a luxury that not everyone can afford, not even those of us who work in healthcare. The system and society measure value by what is useful, fast, and visible. It’s an accelerated society that demands results and considers anything unproductive as inefficient. And in this rhythm — mainly economic, but also symbolic — we’ve inherited a way of understanding health: a “state” achieved by doing more, moving more, accomplishing more, occupying all our time, our body, and our thoughts. Because only by “doing” and being “productive” are we seen as healthy. Without realizing it, even through discourses that aim to be holistic, we’ve reduced health to constant activity — a pattern even replicated by those of us who claim to have a more human, broader, and sensitive perspective. If we are health professionals, not disease professionals, we should ask ourselves: Do all people really need to become more active and less sedentary? What if what they need is not activation, but rest? What if health is not built through movement, but through pause?